Panophthalmitis secondary to retained intraocular foreign body amidst a national lockdown during the COVID-19 pandemic: A case series and review of literature. (May 2022) - Pandit, Kamal; Khatri, Anadi; Sitaula, Sanjeeta; Kharel Sitaula, Ranju; Shrestha, Gulshan Bahadur; Joshi, Sagun Narayan; Karki, Pratap; Rai, Pravin; Chaudhary, Meenu
Abstract: Introduction: Intraocular foreign bodies (IOFBs) can be serious as they may result in vision-threatening ocular inflammations and even loss of the eye. Delay in presentation or treatment by more than 24 hours from the time of injury results in a poor prognosis. In penetrating wounds, microorganisms enter the eye through penetrating objects. Both bacterial and fungal organisms are responsible for causing panophthalmitis. At the ocular level, these microorganisms produce irreversible damage which includes keratitis, uveitis, hypopyon, vitreous abscesses, retinal necrosis, detachment, and, finally, panophthalmitis. Case scenarios: In this case series, we report three cases of IOFB presenting with panophthalmitis secondary to delay in seeking medical attention. In our cases, there was a delay in the presentation by more than 24 hours of trauma. All cases had panophthalmitis at the time of presentation. In two cases, the causative organism was coagulase-negative staphylococci and in one case it was staphylococcus. Initially, we planned to manage them with intravitreous, intravenous and topical antibiotics till the inflammation subsides, then IOFB removal surgeries were planned. However, in two cases, the clinical presentation worsens with scleral necrosis. Therefore, they had to undergo evisceration. In one case, the antibiotics therapy was enough without IOFB removal surgery to manage her symptoms. All cases recovered uneventfully after the interventions. Discussion/Conclusion: In developing nations, like Nepal, transportation barriers can affect a person's access to health care services. This can be clearly explained from this case series as limited transportation options in rural regions are a major factor for all patients' delayed presentation to the hospital during the time of national lockdown in the second wave of the COVID-19 pandemic. The concerned authority must pay attention to solving such social determinants of health. Highlights: Intraorbital foreign bodies can be serious as they may result in vision threatening ocular inflammations and even loss of the eye. Delay in presentation or treatment by more than 24 h from the time of injury results in poor prognosis. Prompt medical and surgical intervention can save vision.